Potential Assessment and Performance Evaluation of a Floating Solar Photovoltaic on the Great Ethiopian Renaissance Dam - Elias Mandefro Getie; Yosef Berhan Jember (International Journal of Photoenergy)
The demand for electricity has increased rapidly in Ethiopia. Renewable energy sources such as solar PV are being used to respond to the power demand and cover a small percentage of the country’s energy need. However, in Ethiopia, where the majority of the land is utilized for agriculture, the land required to generate solar PV power in a large scale is a significant barrier. Big dams, such as Great Ethiopia’s Renaissance Dam, can be used for a solar floating system to eliminate the need for land and transmission infrastructure. Due to its wider area covered by the reservoir, which is about 1,874,000,000 m2, the potential of the renaissance dam needs to be investigated for solar PV floating installation to meet the electricity demand in residential, commercial, and industrial sectors in Ethiopia. In addition, the cooling action of the water on the PV floating allows it to keep its efficiency and increase the power output from the panels. In this study, the performance of grid-connected floating PV systems was evaluated in terms of power generation potential, performance ratio, capacity utilization factor, greenhouse gas emissions, and water conservation. The power consumption of peoples living in the GERD generation site is nearly 1 MW. Though they get electricity through the grid, this study considers performance assessment of a 1 MW solar FPV with the intention of covering the energy need of the hydropower station itself and near rural communities. Modeling and simulation of the proposed FPV plant is done with the help of PVsyst software tool. Finally, the analysis reveals that the GERD has the FPV capability to generate 18,740 MW of maximum power, and its performance was assessed for a 1 MW grid-connected FPV system. The benefits of employing FPV in energy production, water conservation, CO2 emission reduction, and economic benefit are demonstrated in this study. Furthermore, the installation of 1 MW FPV saves 54.4 million liters of GERD water from evaporation per year, which benefits the Blue Nile’s downstream countries to conserve their share of water.